Performance of Optical Wavelength Demultiplexer based on Silicon- on- Insulator (SOI) Microring Resonators (MRRs) - Haroon, Hazura; Hanim, Abdul Razak; Mardiana, Bidin; Sahbudin, Saari; Majlis, B.Y; Menon, P.S (Trans Tech Publications, 2012)
In this paper, we presented the performance analysis of Silicon- on- Insulator (SOI) based, four channels optical wavelength demultiplexer using microrings. The characterizations are done employing Finite- Difference Time- Domain (FDTD) mode simulations from RSOFT. Serially cascaded microring arrays up to the third order are demonstrated to discuss the design issues of the laterally coupled wavelength demultiplexer. Characteristics like the Free Spectral Range (FSR), crosstalk and insertion loss losses are studied.